Inquiry Into Nuclear Generation in Australia Hearing 17 December 2024 - Fullarton, Lex (Parliament of Australia, 2024)
Transcript of the public hearing of the HOUSE OF REPRESENTATIVES SELECT COMMITTEE ON NUCLEAR ENERGY Inquiry into nuclear power generation in Australia TUESDAY, 17 DECEMBER 2024 PERTH Western Australia